GOODS-Herschel~: Gas-to-dust mass ratios and CO-to-H_2 conversion factors in normal and starbursting galaxies at high-z - Magdis, G; Daddi, E; Elbaz, E; Sargent, M; Dickinson, M; Dannerbauer, H; Aussel, H; Walter, F; Hwang, H; Charmandaris, V; Hodge, J; Riechers, D; et al. (2011)
We explore the gas-to-dust mass ratio (G/D) and the CO luminosity-to-Mgas conversion factor (a_co) of two well studied galaxies in the GOODS-N field, that are expected to have different star forming modes, the starburst GN20 at z=4.05 and the normal star-forming galaxy BzK-21000 at z=1.52. Detailed sampling is available for their Rayleigh-Jeans emission via ground based mm interferometry (1.1-6.6mm) along with Herschel, PACS and SPIRE data that probe the peak of their infrared emission. Using the physically motivated Draine and Li (2007) models, as well as a modified black body function, we measure the dust mass (Md) of the sources and find 2.0^{+0.7}_{-0.6} x 10^{9} Msun for GN20 and 8.6^{+0.6}_{-0.9} x 10^{8} Msun for BzK-21000. The addition of mm data reduces the uncertainties of the derived Md by a factor of ~2, allowing the use of the local G\D vs metallicity relation to place constraints on the a_co values of the two sources. For GN20 we derive a conversion factor of a_co < 1.0 Msun pc^{-2}(K km s^{-1})^{-1}, consistent with that of local ULIRGs, while for BzK-21000 we find a considerably higher value, a_co ~4.0 Msun pc^{-2}(K km s^{-1})^{-1}, in agreement with an independent kinematic derivation reported previously. The implied star formation efficiency is ~25 Lsun/Msun for BzK-21000, a factor of ~5-10 lower than that of GN20. The findings for these two sources support the existence of different disk-like and starburst star-formation modes in distant galaxies, although a larger sample is required to draw statistically robust results